Assessing Information Dissemination Channels as Valuable Tools for Educational Development in Nigeria - Danbaba, Shuaib Abdullahi; Titus, Tunnyang Naanfwang; Panshak, Titus Nanpan (NIU Journal of Social Sciences; Vol 8 No 1 (2022): NIU Journal of Social Sciences, Vol. 8 No. 1, March 2022DO - 10.58709/niujss.v8i1.1415, 2022)
Information is a vital tool for the development of education in any society. This paper looked into the meaning of information, information disemination and the difterent channels of information dissemination such as Information Communication Technology (ICT), training and professional preparatory programnnes, mass media, conferences/workshops/seminars and its role to educational development in Nigeria. It also discusses the importance of educational development to national development. Some constraints of informational dissemination channels and recommendations stated. The value of education is underlined by the fact that each society establishes an educational sytstem designed to serve its present and future needs. Education serves as an instrument for stability, change and renewal. Thus, the transmission of knowledge, skills and values is basic and information dissemination has been the key to achieving these laudable goals.